Metabolome and transcriptome association analysis revealed key factors involved in melatonin mediated cadmium-stress tolerance in cotton - Li, Ling; Yan, Xuyu; Li, Juan; Wu, Xiang; Wang, Xiukang (Frontiers in Plant Science, 2022)
Cadmium (Cd), a non-essential element for plant, is a ubiquitous and highly toxic heavy metal, seriously endangering agricultural production and human health. As a nonedible economic crop, cotton (Gossypium hirsutum L.) has great potential in remediation of Cd contaminated soil, but its underlying mechanism is still unknown. Melatonin (MT), as a plant growth regulator, is involved in alleviating Cd toxicity in some plants, but the molecular mechanisms of MT-mediated Cd detoxification in cotton are largely unknown. This study investigated the possible molecular mechanisms of the MT-mediated Cd detoxification in cotton seedlings by comparative transcriptomic and metabolomic analyses. The results showed that the cotton seedlings were short and small, the leaves were withered and yellow under 200 µmol L−1 Cd stress. The application of 50 µmol L−1 MT significantly increased the superoxide dismutase (SOD) activity and malondialdehyde (MDA) content under Cd stress, but 100 µmol L−1 MT significantly decreased SOD activity, while increased ascorbate peroxidase (APX) activity significantly. The Cd concentration were significantly increased in the shoots and roots by adding 100 μmol L−1 MT under Cd stress. RNA-seq analysis showed that 12217 (5573 up- and 6644 down-regulated), 14297 (7105 up- and 7192 down-regulated), 14657 (7253 up- and 7404 down-regulated), 34 (25 up- and 9 down-regulated), 257 (198 up- and 59 down-regulated) and 9 (9 up- and 0 down-regulated) differentially expressed genes (DEGs) were identified in the comparisons of CK vs T1, CK vs T2, CK vs T3, T1 vs T2, T1 vs T3 and T2 vs T3, respectively. It was revealed that MT promoted the expression of certain related genes under Cd stress, and the effect of 100 µmol L−1 MT was better. Moreover, UPLC-MS/MS widely targeted metabolites analyses showed that 211 (195 up-and 16 down-regulated), 161 (150 up-and 11 down-regulated), 173 (150 up-and 23 down-regulated), 50 (12 up-and 38 down-regulated), 151 (24 up-and 127 down-regulated) and 125 (59 up- and 66 down-regulated) differentially accumulated metabolites (DAMs) were changed in the CK vs T1, CK vs T2, CK vs T3, T1 vs T2, T1 vs T3 and T2 vs T3, respectively.